Evaluación técnica y financiera del uso de la herramienta tubing screen en cinco pozos de campo casabe (2018)
Casabe Field is located in the Middle Valley Basin of Magdalena of Colombia, began its commercial exploitation in 1945. It has water injection as a secondary recovery form, since 1980. It is currently operate by the alliance Ecopetrol S.A. – Schlumberger. Throughout this project you can find a description of the field and the current conditions together with the geological characteristics of this. Starting from the description of the techniques used in Colombia for the control of the configuration of the technology of the Tubing screen, consult the information referring to the conditions in which all the times are found before being intervened, as well as the description of the design and implementation of the tool in the five wells. The system of artificial lift of each of the wells was studied, taking into account the negative impact that the sand grains have on the different parts of the system. For the description of the implementation of the tool you can use the tubing Screen Calculator, which by means of the information of the design criteria for each well, establish the number of joints necessary to install, in order to complete the tool with the main objective of controlling the sand particles before entering the artificial lift system for the production the fluid with sand and damage to the equipment of the artificial lift system.